(untitled) (Sociologisk Forskning, 1994)
Solidarity in intergenerational studies - a concept under debate In intergenerational studies the concept of ’solidarity’ has been crucial in analyses of the relations between the generations. The concept of ’solidarity’ is based on Durkheim’s concept of ’mechanic solidarity’, and is developed out of theories about cohesion in small groups presuming connections between contact, affection and value similarity. The concept of ’intergenerational solidarity’ is assumed to be a single higher-order construct of various dimensions correlated with each other. Some earlier empirical studies fail to support these presumptions, which in spite of this has not led to a critical discussion, or reconsideration of the theoretical presumptions of this concept. The purpose of this presentation is to put the concept of ’intergenerational solidarity’ under debate in the light of these earlier results and of empirical results from a Swedish survey conducted in three family generations. The survey includes two parent generations; one older and one middle-aged, and two child generations; the middle-aged ones and one younger generation, totally 888 subjects between 15 and 97 years of age. The analyses show that presumed connections between the various solidarity dimensions are lacking. The lack of correlations refer especially to the parent generations, and to a lesser degree to the child generations, which might be explained by the asymmetric relationship between parents and children. Theoretically, this lack of correlation might be due to its origin in small group theory and its presumption of voluntary group membership. Family and kinship relations are not voluntary, and as intergenerational relationships are asymmetric, it would be difficult to find a unitary and higher-order concept suitable for both parents and children. The analysis suggests that Durkheim’s concept of ’mechanic solidarity’ does not apply to family and kinship relations. The conclusion is that some of the theoretical presumptions concerning the concept of ’intergenerational solidarity’ are not applicable to family and kinship relations. As an alternative to the concept of ’solidarity’, Weber’s concepts of Vergemeinschaftung and Vergesellschaftung are suggested.